Effect of ark clam shell on crystal growth and mechanical evaluation of foam glass-ceramic derived from cullet glass waste - N. Hisham, N. A.; M. Zaid, M. H.; Matori, K. A.; Shabdin, M. K. (Elsevier, 2022)
The solid-state sintering technique was used to successfully manufacture low-cost foam glass-ceramic utilising ark clamshell and cullet glass waste. The foam glass-ceramic has a composition of xACS-(100-x)SLS, where x = 1, 3, 6, and 9 wt%, and is classified as FGC1, FGC2, FGC3, and FGC4 as the ark clamshell content increases. The X-ray diffraction (XRD) and Fourier transform infrared (FTIR) findings reveal that when the ark clamshell composition increases, two main crystals with the appearance of Csingle bondO and Casingle bondOsingle bondSi bands grow as wollastonite (CaSiO3) and cristobalite (SiO2) phases. Field emission scanning electron microscope (FESEM) micrograph was used to confirm the porosity microstructure of the foam glass-ceramic aggregates. The sample with the greatest expansion (83.98%) yielded the lowest apparent density (0.699 g/cm3). The compressive strength measurement of the foam glass-ceramic aggregates was measured using GCF2 with 3 wt% of ACS. For a sample containing 3 wt% ACS, the maximum compressive strength value was 1.14 MPa, with an average total porosity of about 58.34%, and it has the potential to be employed in the construction sector.